ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRES KERJA PADA KARYAWAN - Maximilianus Dasril Samura; Finency Sitompul (Jurnal Inovasi Kesehatan Masyarakat, 2020)
Stress due to work is a physical and emotional disturbance as a result of a mismatch between the capacity, resources or needs of workers who come from the work environment. Research conducted by Utami (2017), there were 54.1% of workers experiencing heavy work stress and 45,9% of workers experiencing mild work stress. Stress management is very important so that workers do not experience heavy work stress. This research design uses Cross Sectional. The study population numbered 264 people and the study sample numbered 73 people. The sampling technique is to use Simple Random Sampling. Data analysis was performed univariate, bivariate (using Chi Square α = 0.05) and multivariate (Logistic Regression). Based on the chi square test, the factors that influence work stress (p < 0.05) are abilities that are not used (p = 0.028), interpersonal relationships (p = 0.010), job uncertainty (p = 0.013) and factors that are not affecting work stress are age (p = 0.390), work period (p = 0.979), social support (p = 0.907). The results showed that there were 3 candidates who entered into multivariate analysis modeling, namely the ability not used, interpersonal relationships, and job uncertainty. While the most dominant or influential factor with work stress is interpersonal relationships. Researchers suggest that the company and employees implement effective communication to avoid conflict so that interpersonal relationships will be better.